2015
DOI: 10.1074/jbc.m114.617746
|View full text |Cite
|
Sign up to set email alerts
|

Specific Activation of the Plant P-type Plasma Membrane H+-ATPase by Lysophospholipids Depends on the Autoinhibitory N- and C-terminal Domains

Abstract: Background: Lysophospholipids activate P-type plasma membrane H ϩ -ATPase proton pump by an unknown mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…The monoacyl signaling lipid lysophosphatidylcholine was the first factor found to activate the plant PM H + -ATPase (Palmgren and Sommarin, 1989). In vitro, lysophospholipids directly relieve the autoinhibitory effect of both the N-and C-terminal domains (Wielandt et al, 2015). Although lysophospholipids are the most potent activators of the PM H + -ATPase identified to date, the physiological relevance of lysophospholipids in PM H + -ATPase regulation is uncertain.…”
Section: Regulation By Lipidsmentioning
confidence: 99%
“…The monoacyl signaling lipid lysophosphatidylcholine was the first factor found to activate the plant PM H + -ATPase (Palmgren and Sommarin, 1989). In vitro, lysophospholipids directly relieve the autoinhibitory effect of both the N-and C-terminal domains (Wielandt et al, 2015). Although lysophospholipids are the most potent activators of the PM H + -ATPase identified to date, the physiological relevance of lysophospholipids in PM H + -ATPase regulation is uncertain.…”
Section: Regulation By Lipidsmentioning
confidence: 99%
“…There are also other explanations that would account for our results. For example, it is known that detergents can activate membrane transporters (27). Thus, it is possible that detergent solubilization (the first step in obtaining purified protein after expression in yeast) converts nhTMEM16 into a partially active conformation and that this conformation is preserved even after detergent removal and reconstitution.…”
Section: Resultsmentioning
confidence: 99%
“…One can imagine that TeA binds to a site generated between the body of the protein and is stabilized by the C‐terminus. We have previously demonstrated that lysophospholipids can activate the plant PM H + ‐ATPase, whereas they do not have any effects on the fungal Pm H + ‐ATPase (Wielandt et al , ). Additionally this regulation involved the regulatory C‐terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…H + ‐ATPase activity was assayed according to the modified protocol of Baginski et al () described by Wielandt et al (). For each well, 0.5–3 μg of protein was added in a 60 μl volume.…”
Section: Methodsmentioning
confidence: 99%